The role of the International Monetary Fund in the post-crisis world - Mark Kruger; Robert Lavigne; Julie McKay (Bank of Canada, 2016)
The International Monetary Fund (IMF, or the Fund) has undergone a number of significant policy changes and reforms in the wake of the global financial crisis. Most notably, in December 2015, the United States approved long-delayed legislation to increase the representation of developing countries in the Fund's governance structure. The vital progress on quota shares has finally allowed for a resumption of wider and increasingly critical discussion of the strategic role of the IMF in the post-crisis world. This paper aims to relaunch the debate by assessing the recent reforms and changes, identifying areas where progress is still needed and proposing solutions. Our findings suggest that, while much has been accomplished by the Fund's management and staff since the global crisis, there is still a pressing need for member countries to push for further reforms if the IMF is to remain a relevant player in the rapidly evolving global economic and financial system. Emerging-market economies remain under-represented at the Fund and continue to perceive the IMF as biased against them, undermining the influence of its advice, despite the increase in their quota share and changes to improve the quality, efficiency and even-handedness of the IMF's surveillance and lending. In advanced economies, where the Fund has traditionally had little traction on national policies, the institution faces the challenge of managing and communicating its independence in programs involving large shareholders. We propose reforms aimed at improving country representation, granting the IMF real operational independence and enhancing its catalytic role.
Keywords: F; F3; F33; 330; International topics